Multi-Modality Imaging for Interventions in Tricuspid Valve Disease - Fortuni, Federico; Hirasawa, Kensuke; Bax, Jeroen J.; Delgado, Victoria; Ajmone Marsan, Nina (Frontiers in Cardiovascular Medicine, 2021)
Several studies have demonstrated that severe tricuspid regurgitation (TR) has a significant negative impact on morbidity and mortality. Nowadays, several therapeutic options to treat TR are available and patients at high surgical risk can also be treated with transcatheter procedures. For the management of patients with TR, an accurate assessment of the tricuspid valve and its surrounding structures is therefore of crucial importance and has gained significant interest in the medical community. Different imaging modalities can provide detailed information on the tricuspid valve apparatus, right ventricle, right atrium and coronary circulation which are fundamental to define the timing and anatomic suitability of surgical and percutaneous procedures. The present review illustrates the role of 2D and 3D echocardiography, cardiac magnetic resonance and multidetector row computed tomography for the assessment of the tricuspid valve and right heart with a particular focus on the data needed for planning and guiding interventional procedures.